Violence, women and gender roles in Pamplona during the Second Republic - Aldave Monreal, Esther (Huarte de San Juan. Geografía e Historia, 2020)
The relative openness in the political context during the Second Republic regarding women’s rights contrasted with the permanence that existed within socially accepted models of femininity. The dynamics of daily violence to which many women were exposed, as well as their role as an active subject in the commission of violent acts, are a good way to explore this historical period and its contrasts from a microperspective in order to promote new lines of research. To do so, we will set some paradigmatic cases in a local level following some thesis provided from gender theories and sociocultural history. Different sources will be used, such as judicial documents and newspapers, which are interesting not only for the information they provide, but also for spreading normative discourses regarding gender roles.
Keywords: woman; violence; Second Republic; Pamplona; gender